2006
DOI: 10.1021/ol052851n
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis, Structural Revision, and Absolute Configuration of (+)-Clavosolide A

Abstract: [reaction: see text] Enantioselective synthesis of 3, a revised structure for clavosolide A, was completed. Both (1)H and (13)C NMR spectra of the natural and synthetic compounds were identical, and optical rotation measurements identified the absolute configuration of the natural clavosolide A as [corrected] 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 33 publications
2
27
0
1
Order By: Relevance
“…Structural motifs misassigned on the basis of NOEs include epoxides (calafianin, 9698 symbiodinolide 99, 100 ), cyclopropyl rings (clavosolide A, 101, 102 laurentristich-4-ol 103, 104 ), bridges (vannusals A and B 105107 ), fused ring junctions (itomanallene A, 108, 109 asperdimin, 110, 111 aplysiallene 112, 113 ), polyethers (aplysiol B, 114, 115 azaspiracids 116119 ), vicinal polyols (amphidinolide H2, 120, 121 hyrtiosterol, 122, 123 pericosine A 124, 125 ), sugars (callipeltoside C; 126, 127 fusapyrone and deoxyfusapyrone, 128, 129 Table 6) and macrolides (palmerolide A, 130132 neopeltolide 133, 134 ).…”
Section: Sources Of Natural Product Structural Misassignmentsmentioning
confidence: 99%
“…Structural motifs misassigned on the basis of NOEs include epoxides (calafianin, 9698 symbiodinolide 99, 100 ), cyclopropyl rings (clavosolide A, 101, 102 laurentristich-4-ol 103, 104 ), bridges (vannusals A and B 105107 ), fused ring junctions (itomanallene A, 108, 109 asperdimin, 110, 111 aplysiallene 112, 113 ), polyethers (aplysiol B, 114, 115 azaspiracids 116119 ), vicinal polyols (amphidinolide H2, 120, 121 hyrtiosterol, 122, 123 pericosine A 124, 125 ), sugars (callipeltoside C; 126, 127 fusapyrone and deoxyfusapyrone, 128, 129 Table 6) and macrolides (palmerolide A, 130132 neopeltolide 133, 134 ).…”
Section: Sources Of Natural Product Structural Misassignmentsmentioning
confidence: 99%
“…Literature precedent for the synthesis of (−)‐clavosolide A and (−)‐cyanolide A indicated that the glycosylation of the symmetrical parent diol of a bis‐macrolactone precursor led to a statistical mixture of [ α,α ]‐, [ β,β ]‐, and [ α,β ]‐anomers, which reduced the overall yield of the total synthesis . Thus, in designing the synthetic strategy to cocosolide we aimed to close the macrocycle via the dimerization of the permethylated‐ d ‐xylose‐containing monomer 21 , which could be obtained from glycosylation of alcohol 19 .…”
Section: Resultsmentioning
confidence: 99%
“…This methodology has been applied to the total synthesis of several natural polyketides, including leucascandrolide A [52], clavosolide A [53], peloruside A [54], dolabelide D [55], and oasomycin A [56].…”
Section: ) [48]mentioning
confidence: 99%